THE PROCEDURE FOR ACCOUNTING FOR FIXED ASSETS IN MANUFACTURING ENTERPRISES BASED ON INTERNATIONAL STANDARDS (World Economics and Finance Bulletin, 2026)
This article explains the procedure for classifying, receiving, accounting for, and reflecting fixed assets in the accounting policies of manufacturing enterprises. It also details how to make the appropriate entries in bookkeeping and formulate the relevant indicators in financial statements. Furthermore, the theoretical and practical aspects of accounting for fixed assets based on international standards are examined. Specifically, the procedures for the recognition, measurement, revaluation, and derecognition of fixed assets are analyzed within the framework of International Financial Reporting Standards, including the requirements of IAS 16 Property, Plant and Equipment. Issues related to determining the initial cost of fixed assets, capitalizing subsequent expenditures, methods of calculating depreciation, and asset impairment are also covered.
Keywords: Accounting; bookkeeping; International Financial Reporting Standards; types of fixed assets